ROCK‐TAZ signaling axis regulates mechanical tension‐induced osteogenic differentiation of rat cranial sagittal suture mesenchymal stem cells. Issue 9 (22nd January 2020) - Li, Wenlei; Zhao, Jing; Wang, Jialu; Sun, Lian; Xu, Haiyang; Sun, Wen; Pan, Yongchu; Wang, Hua; Zhang, Wei‐Bing
Abstract: Mechanical force across sutures is able to promote suture osteogenesis. Orthodontic clinics often use this biological characteristic of sutures to treat congenital cranio‐maxillofacial malformations. However, the underlying mechanisms still remain poorly understood. Craniofacial sutures provide a special growth source and support primary sites of osteogenesis. Here, we isolated rat sagittal suture cells (rSAGs), which had mesenchymal stem cell characteristics and differentiating abilities. Cells were then subjected to mechanical tension (5% elongation, 0.5 Hz; sinusoidal waveforms) showing that mechanical tension could enhance osteogenic differentiation but hardly affect proliferation of rSAGs. Besides, mechanical tension could increase Rho‐associated kinase (ROCK) expression and enhance transcriptional coactivator with PDZ‐binding motif (TAZ) nuclear translocation. Inhibiting ROCK expression could suppress tension‐induced osteogenesis and block tension‐induced upregulation of nuclear TAZ. In addition, our results indicated that TAZ had direct combination sites with runt‐related transcription factor 2 (Runx2) in rSAGs, and knock‐downed TAZ simultaneously decreased the expression of Runx2 no matter with or without mechanical tension. In summary, our findings demonstrated that the multipotency of rSAGs in vitro could give rise to early osteogenic differentiation under mechanical tension, which was mediated by ROCK‐TAZ signal axis. Abstract : The multipotent rat sagittal suture cells (rSAGs) in vitro could give rise to early osteogenic differentiation under mechanical tension. ROCK‐TAZ signal axis was involved in regulating the process.